TERANG : Discover Your Passion, Ignite Your Academic Enthusiasm Through Group Counseling - Anindita, Tanaya; Febriyanti, Safiah; Haq Filhal, Najwa; Pratiwi Kuswardani, Hasna' (Educational Psychology Journal, 2025)
This study aims to examine the effectiveness of group counseling program TERANG (Discover Your Passion, Ignite Your Academic Enthusiasm) in improving academic motivation of vocational high school students. Using a quasi-experimental design with pre-test and post-test, five students from accounting major in SMK X Semarang participated. Data were collected using Academic Motivation Scale (AMS), interviews, and observations. Results of paired sample t-test revealed a significant increase in academic motivation (p = 0.018), with three students achieving high category after intervention. The findings indicate that group counseling creates a supportive environment that enables students to share experiences, gain insights, and build adaptive strategies to enhance academic enthusiasm. This study highlights the role of the humanistic approach in counseling to foster motivation, and contributes to educational psychology by providing evidence of group counseling effectiveness in vocational context.